2018
DOI: 10.1101/378109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autoimmunity to hypocretin and molecular mimicry to flu antigens in Type 1 narcolepsy

Abstract: was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…When the authors analysed samples of CD4 + T cells, they found that the proportion of these cells that recognize hypocretin was more than ten times higher in individuals with narcolepsy than in control individuals. This increased Tcell reactivity to hypocretin has also been reported independently 12 , and strongly suggests that auto immunity has a role in narcolepsy.…”
Section: Put To Sleep By Immune Cellssupporting
confidence: 76%
See 1 more Smart Citation
“…When the authors analysed samples of CD4 + T cells, they found that the proportion of these cells that recognize hypocretin was more than ten times higher in individuals with narcolepsy than in control individuals. This increased Tcell reactivity to hypocretin has also been reported independently 12 , and strongly suggests that auto immunity has a role in narcolepsy.…”
Section: Put To Sleep By Immune Cellssupporting
confidence: 76%
“…Maybe an initial Tcell response to hypo cretinproducing neurons is dominated by T cells that recognize antigens bound to HLADQ6, but over time the response shifts to T cells that recognize antigens presented on HLADR. An observation consistent with this model is the recent report 12 that the propor tion of T cells that respond to hypocretin pre sented by HLADQ6 is higher than normal in people with recentonset narcolepsy. Another possibility is that T cells in the bloodstream (tested by the authors) have different HLA binding preferences from those in the brain.…”
Section: Put To Sleep By Immune Cellssupporting
confidence: 76%
“…Several studies have identified a single nucleotide polymorphism in the gene encoding the TCR α-chain that roughly doubles the risk of NT1 (REFS 152154 ), suggesting that NT1 might arise from an interaction of DQB1*06:02 and specific TCRs. Further, according to preliminary work, specific, rare single nucleotide polymorphisms within the TCR genes may greatly increase the reactivity of T cells to fragments of the orexin neuropeptides 155 . NT1 risk is also associated with variants of the gene coding for cathepsin H, an enzyme involved in digesting proteins into smaller peptides that can be presented by MHC class II molecules 154 .…”
Section: Evidence For An Autoimmune Mechanismmentioning
confidence: 99%
“…In conclusion, we provide preliminary evidence for the involvement of RFX4 in T1N in some subjects through both anti-RFX4 autoantibody detection and tetramer DQ0602-strong RFX4 binders staining. Most notable was the enrichment of TRBV4-2, which we have previously shown to be genetically associated with T1N (13) and involved in T cell recognition of HCRT-NH2 in this disorder (46) , hence suggesting causality. We propose an involvement of T cell reactivity against specific RFX4 peptides in the pathophysiology of some T1N cases.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast to the findings concerning antibody-mediated immunity, adaptive cell-mediated immunity has been increasingly and robustly implicated in the pathophysiology of narcolepsy (44,45), a result that fits well with genetic data indicating association with HLA and TCR loci. Thanks to HLA class I and II multimers and fluorescence-activated cell sorting (FACS)-based single cell sorting and sequencing technologies, investigation of cellular immune responses to infectious agents and autoantigens in autoimmune diseases is now possible in more details (46,47). Specifically, tetramer HLA-targeted T cells facilitates identification of antigen specific TCRgroups within highly diverse TCR repertoires (48,49), which are stochastically generated by V(D)J recombination, a process rearranging germline TCR loci in each T cell (50,51).…”
Section: Introductionmentioning
confidence: 99%